PELATIHAN BAHASA INGGRIS KEPARIWISATAAN BAGI PELAKU WISATA DI KAMPUNG HERITAGE KAYOETANGAN KOTA MALANG - Degeng, Putu Dian Danayanti; Irene Nany Kusumawardani; Moh. Hasbullah Isnaini; Galuh Indah Asri (LPPM Universitas PGRI Adi Buana Surabaya, 2022)
The tourism development in Malang thematic villages is still not supported by the quality of the tourism doers. Based on the data from Kelompok Sadar Wisata in Kampoeng Heritage Kayoetangan, many tourism workers who also the front-liners are still not mastering the foreign language, especially English. This reality will influence the service quality for the foreigner. The best solution to this problem is by having English for Tourism and Hospitality workshop which assists them to provide better service. The theme for the workshop were English for Culinary and Hospitality.This topic was chosen based on the people’s need. Many tourism workers in this place own food stalls, yet they do not know how to speak English well to promote the products. This workshop was conducted in August-September 2019 and 20 people participated. The participants learnt the theory of Hospitality in English and practiced it within eight meetings. This community service was conducted based on the agreement of Faculty of Cultural Studies Universitas Brawijaya (FIB UB) and Malang Department of Culture and Tourism.